Kesehatan Karang Kondisi Kesehatan Terumbu Karang Daerah Wisata Selam Pulau Bunaken Sulawesi Utara - Youdy Joseph Hendrik Gumolili (PolimdoSains, 2019)
This research has been held in Eastern site of Bunaken Island coral reef area at May 22-28 2018. Using PIT method (Point Intercept Transect) in 5 meter depth with 25 m transect long. Research result show that in general coral health level at coral reef area in Eastern site Bunaken Island around 41.2 % and average unhealthy coral above 15 colony each transect. This fact show that condition of coral health in that area well off at fair category. Key words: Healty coral, Point Intercept Transect, Fair Category.